Frequency Splitting Analysis of Wireless Power Transfer System Based on T-type Transformer Model - Jianyu, Lan; Houjun, Tang; Xin, Gen (Elektronika ir Elektrotechnika, 2013)
Frequency splitting is a key characteristic of wireless power transfer system. With the increases of coupling coefficient, the power transferred to load drops sharply. The resonant frequency splits from one into two within splitting region. Previous reports about frequency splitting mainly focused on the analysis of coupled mode theory or the solutions of ridge equations. In this work, we presented the analytical results based on a simply T-type circuit model. With impedance analysis, the even and odd splitting frequencies were derived. In addition, the frequency splitting phenomena were analysed with output voltage curves at different coupling by the aid of simulation. Furthermore, the frequency splitting and the frequency bifurcation discussed frequently in inductively coupled wireless power transfer system were analysed comparatively based on the circuit model. Then, a half-bridge inverter based wireless power system was constructed to demonstrate the experimental results. Finally, the simulation and experimental results validated the theoretical analysis. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5455